2007
DOI: 10.3354/cr033135
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and severity of drought in the Lake Victoria region (Kenya) and its effects on food security

Abstract: Using monthly and seasonal precipitation data for the period 1961-1999, we established drought frequency and severity in relation to food security in the Lake Victoria region in Kenya. We used percentiles together with time series analysis for a 40 yr period, with the lower 25% of the quartile designated as the threshold values that indicate drought years. We then used percentiles and Drought Severity Index (DSI) to ascertain the physical conditions and severity of the drought years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…There are a Kayombo and Jorgensen, 2006) number of other meteorological stations within the LVB, but all are found in the same (Lake Victoria) climatological zone with homogeneous anomalies. Past studies have shown significant homogeneity in the patterns of rainfall anomalies in East Africa including Lake Victoria basin, resulting into common use of single rain gauge location to represent large areas (Ogallo 1988(Ogallo , 1993Basalirwa et al 1993;Awange et al 2007b). Several authors have also noted that large scale moisture transported by monsoonal winds enhance basin precipitation significantly.…”
Section: Data Sourcementioning
confidence: 95%
See 1 more Smart Citation
“…There are a Kayombo and Jorgensen, 2006) number of other meteorological stations within the LVB, but all are found in the same (Lake Victoria) climatological zone with homogeneous anomalies. Past studies have shown significant homogeneity in the patterns of rainfall anomalies in East Africa including Lake Victoria basin, resulting into common use of single rain gauge location to represent large areas (Ogallo 1988(Ogallo , 1993Basalirwa et al 1993;Awange et al 2007b). Several authors have also noted that large scale moisture transported by monsoonal winds enhance basin precipitation significantly.…”
Section: Data Sourcementioning
confidence: 95%
“…The 30-years' mean was in accordance with World Meteorological Organization (WMO) requirement that this be the standard used to define the rainfall 'normal' of a region (Awange et al 2007b). Using Eqs.…”
Section: Analysis Approachmentioning
confidence: 99%
“…Personal communication to local people explains that in the past, the Simiyu River maintained notable annual water flow however, the current situation observed during this study, showed reduced and stagnant water pools during dry months of the year (June -August) and significant water discharge only during the rainy season (March -May). This is explained to be associated with agricultural activities being undertaken along the river basin and reduced rainfall in the region due to climatic changes in the region (Swenson and Wahr, 2009;Awange et al, 2007;2008). Sampling of surface Lake water was done during periods of high runoff (MarchApril) and periods of low runoff (JuneAugust) in 2007 -2009.…”
Section: Materials and Methods Study Area And Samplingmentioning
confidence: 99%
“…Despite the episodes of flooding, low flows tend to subsequently punctuate the basin's hydrology often for long periods of time. Severe droughts in the Lake Victoria basin can be expected on average about every seven to eight years during the hot dry season from December to February [35]. According to Otieno and Awange [36], these droughts affected power production with resulting economic losses.…”
Section: Study Area and Data Seriesmentioning
confidence: 99%
“…According to Otieno and Awange [36], these droughts affected power production with resulting economic losses. According to Awange et al [35], Lake Victoria and its environment is more recently under threat from declining water levels, which has had a number of social and economic effects.…”
Section: Study Area and Data Seriesmentioning
confidence: 99%